Functionality, quality of life and psychological health of elderly people in the context of social isolation: integrative review (Research, Society and Development, 2023)
Introduction: the World Health Organization (WHO) considers an elderly person to be an inhabitant of a developing country who is 60 years old or older and an inhabitant of a developed country who is 65 years old or older. With the emergence of the new coronavirus, SARS-CoV-2, social isolation has become the most recommended means of preventing its transmissibility, with the elderly being the most vulnerable population. Objective: to analyze the association between social isolation that occurred during the COVID-19 pandemic, with functionality, quality of life (QoL) and psychological health of the elderly population. Methods: integrative review of observational studies published between 2020-2022 in any language, with the combination of specific terms and keywords for this review, using the Boolean operators OR and AND. A search was performed in PubMed, Embase, CENTRAL, CINAHL, Web of Science, Science Direct, PEDro and BVS databases. Results: of the 11,391 records identified, 2,801 were removed because they were duplicates, leaving 8,590 studies for evaluation by title and abstract, of which 8,484 were excluded for not addressing the theme suggested in this review, with 106 studies being analyzed with the full text, so at the end 15 articles were included in the integrative review. Conclusion: the context of social isolation related to the COVID-19 pandemic scenario brought with it reductions in QoL, as well as in the physical and mental health of the elderly population. Therefore, the results of this review can contribute to the decision-making process regarding prevention and health promotion actions for the elderly.